Resources of Boti Village (Timor Island) for the Ecotourism Development - Simon Suddin (Journal of Indonesian Tourism and Development Studies, 2017)
The aim of the paper is to describe the natural and cultural resources of Boti community for tourism development in Boti Village in Timor Island, Indonesia. Boti has been known as the last kingdom in Timor Island and has visited by tourist to enjoy community live and green landscape in semi arid region in Timor Island. The Boti community has indigenous belief called halaika, and community daily life was organized and managed by a king called Usif. The basic philosophy of community who live in Boti was implemented in house structure, arrangement and philosophy (sonaf, ume kbubu, lopo), farming activity, and many daily activities. The uniqueness of Boti’s nature and culture has potentiality to be developed as tourism attractions. The local wisdoms of local community in Boti influence the sustainable uses of resources, in which it is produces green and beauty forest landscape in Boti area. Eco-tourism seems to be potential form of tourism in Boti villages.Keywords: Boti Village, ecotourism, indigenous community, local wisdom.